ANALYSIS OF THE EFFECTIVENESS OF BUDGET USE IN THE HEALTH PERSONNEL NEEDS PLAN AT INTAN JAYA DISTRICT HOSPITAL, CENTRAL PAPUA PROVINCE - Samuel, Saman Bte; Baharuddin, Baharuddin; Rantererung, Corvis L (Entrepreneurship Undergraduate Program at Amkop Business School, 2025)
This study aims to analyze the effectiveness of budget use in the health worker needs plan at Intan Jaya District Hospital, Central Papua Province. The research method used is qualitative with a descriptive approach. Data were collected through observation, in-depth interviews with five key informants, and analysis of related documents. The results of the study indicate that the effectiveness of budget use in meeting the needs of health workers at Intan Jaya District Hospital still faces various challenges, such as limited budget allocation, gaps between budget plans and realization, and the mismatch between the number of health workers and existing needs. Factors that support the effectiveness of budget use include accurate budget planning, strong management support, involvement of health workers in planning, transparency and accountability, flexibility in budget use, and ongoing monitoring and evaluation. The impact of budget use on the availability and quality of health workers includes an increase in the number of medical personnel, but there is still a gap in the welfare and incentives of health workers due to suboptimal budget allocation. Therefore, a more adaptive policy is needed in budget planning and management to ensure adequate health workers and quality health services for the community in Intan Jaya Regency.Keywords: Effectiveness, Budget, Health Workers, Regional Public Hospital, Central Papua